Default Dispute Settlement Through Somasi (Somatie Or Legal Notice) Based On Law 1238 Of The Civil Code - Gunawan Nasution, Sakti; Risdalina, Risdalina; Kumalasari M, Indra (International Journal of Educational Research & Social Sciences, 2022)
This study aims to find out and analyze the settlement of default disputes through subpoena (somatie or legal notice) and analyze the legal protection of debtors' defaults. This research is a type of normative research. So that it can be seen that legal protection against debtor default is divided into two, namely preventive legal protection (prevention) and repressive (settlement). Apart from that, there is also rescheduling, reconditioning and restructuring. In addition, settlement of default disputes through subpoena (somatie or legal notice) is legal. However, subpoena does not have the nature of execution, because only as a warning, therefore it can be resolved by means of litigation and non-litigation.